Repurchase Intention of Tokopedia Customers: An Overview of The Effect of Brand Image and Electronic Word of Mouth Through Customer Satisfaction - Valentio, Velycia; Erwita, Monica Adjeng (JEM17: Jurnal Ekonomi Manajemen, 2024)
This study examines the effect of brand image and electronic word of mouth on repurchase intentionthrough customer satisfaction on Tokopedia. The research objects are all Tokopedia consumers inSurabaya who have made at least one purchase through Tokopedia. The data analysis technique usesStructural Equation Modeling - Partial Least Square (SEM-PLS). The results showed that brand imageaffects customer satisfaction and repurchase intention, electronic word of mouth does not affect customersatisfaction and repurchase intention, and customer satisfaction affects repurchase intention. Brandimage affects repurchase intention through customer satisfaction, while electronic word of mouth doesnot affect repurchase intention through customer satisfaction for Tokopedia consumers. Keywords: Brand Image; Customer Satisfaction; Electronic Word of Mouth; Repurchase Intention